2023
DOI: 10.1021/jacsau.3c00473
|View full text |Cite
|
Sign up to set email alerts
|

Ternary Heterostructure Membranes with Two-Dimensional Tunable Channels for Highly Selective Ion Separation

Huiling Liu,
Xin Zhang,
Zixiao Lv
et al.

Abstract: Selective ion separation from brines is pivotal for attaining high-purity lithium, a critical nonrenewable resource. Conventional methods encounter substantial challenges, driving the quest for streamlined, efficient, and swift approaches. Here, we present a graphene oxide (GO)-based ternary heterostructure membrane with a unique design. By utilizing Zn2+-induced confinement synthesis in a two-dimensional (2D) space, we incorporated two-dimensional zeolitic imidazolate framework-8 (ZIF-8) and zinc alginate (ZA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…Over the past few decades, advances in nanofabrication and synthesis have greatly facilitated the research on nanofluidics, which can manipulate ion flows at length scales of <100 nm. In nanofluidic ion channels, dominant intermolecular forces, such as steric interactions, hydration, van der Waals, and electrostatic interactions, endow them with unique selective mass transport capabilities. These properties make nanofluidic ion channel membranes promising in various applications, including water purification, energy conversion, molecular sensing, , and resource recovery. , Among them, the nanofluidic energy harvesting of salinity gradients has experienced considerable research interest in recent years due to its high energy conversion efficiency and power density. Fundamental studies on single-pore nanofluidic membranes have shown that nanofluidic membranes promise to achieve an ultrahigh power output. For example, a single-layered MoS 2 sheet with a single nanopore has achieved an output power density of 10 6 W/m 2 , which is several magnitudes higher than conventional ion-exchange membranes . Nevertheless, to scale up these single-nanopore devices for practical use, two major hurdles need to be overcome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past few decades, advances in nanofabrication and synthesis have greatly facilitated the research on nanofluidics, which can manipulate ion flows at length scales of <100 nm. In nanofluidic ion channels, dominant intermolecular forces, such as steric interactions, hydration, van der Waals, and electrostatic interactions, endow them with unique selective mass transport capabilities. These properties make nanofluidic ion channel membranes promising in various applications, including water purification, energy conversion, molecular sensing, , and resource recovery. , Among them, the nanofluidic energy harvesting of salinity gradients has experienced considerable research interest in recent years due to its high energy conversion efficiency and power density. Fundamental studies on single-pore nanofluidic membranes have shown that nanofluidic membranes promise to achieve an ultrahigh power output. For example, a single-layered MoS 2 sheet with a single nanopore has achieved an output power density of 10 6 W/m 2 , which is several magnitudes higher than conventional ion-exchange membranes . Nevertheless, to scale up these single-nanopore devices for practical use, two major hurdles need to be overcome.…”
Section: Introductionmentioning
confidence: 99%
“…7−9 These properties make nanofluidic ion channel membranes promising in various applications, including water purification, 10−12 energy conversion, 13−15 molecular sensing, 16,17 and resource recovery. 18,19 Among them, the nanofluidic energy harvesting of salinity gradients has experienced considerable research interest in recent years due to its high energy conversion efficiency and power density. 20−22 Fundamental studies on single-pore nanofluidic membranes have shown that nanofluidic membranes promise to achieve an ultrahigh power output.…”
Section: ■ Introductionmentioning
confidence: 99%
“… 19 In scenarios involving mixed ion systems, the determination of the GO membrane's interlayer spacing hinges upon the initial entry of metal ions into the interlayer space. 35 However, the flexible nature of materials such as GO implies that the size screening effect alone fails to comprehensively account for all observed separation phenomena. Consequently, it is imperative to posit the existence of an alternative separation mechanism beyond the confines of the size screening effect.…”
Section: Introductionmentioning
confidence: 99%